Isolated Focal Dystonia as a Disorder of Large-Scale Functional Networks. (17th December 2015) - Battistella, Giovanni; Termsarasab, Pichet; Ramdhani, Ritesh A.; Fuertinger, Stefan; Simonyan, Kristina
Abstract: Isolated focal dystonias are a group of disorders with diverse symptomatology but unknown pathophysiology. Although recent neuroimaging studies demonstrated regional changes in brain connectivity, it remains unclear whether focal dystonia may be considered a disorder of abnormal networks. We examined topology as well as the global and local features of large-scale functional brain networks across different forms of isolated focal dystonia, including patients with task-specific (TSD) and nontask-specific (NTSD) dystonias. Compared with healthy participants, all patients showed altered network architecture characterized by abnormal expansion or shrinkage of neural communities, such as breakdown of basal ganglia–cerebellar community, loss of a pivotal region of information transfer (hub) in the premotor cortex, and pronounced connectivity reduction within the sensorimotor and frontoparietal regions. TSD were further characterized by significant connectivity changes in the primary sensorimotor and inferior parietal cortices and abnormal hub formation in insula and superior temporal cortex, whereas NTSD exhibited abnormal strength and number of regional connections. We suggest that isolated focal dystonias likely represent a disorder of large-scale functional networks, where abnormal regional interactions contribute to network-wide functional alterations and may underline the pathophysiology of isolated focal dystonia. Distinct symptomatology in TSD and NTSD may be linked to disorder-specific network aberrations.